2013
DOI: 10.1590/s0034-72802013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de algumas drogas sobre a proliferação de fibroblastos de pterígio primário in vitro

Abstract: Objective: This study aims at observing the inhibition of cell proliferation in primary pterygium by the use in vitro of RESUMOObjetivo: Este estudo tem por objetivo observar a inibição da proliferação celular in vitro em pterígios primários utilizando mitomicina C, ciclofosfamida e metotrexato. Métodos: Os pterígios foram retirados de 7 pacientes com idade entre 30 e 60 anos e foram submetidos à cultura de suas células epiteliais. Foi então verificado o efeito de drogas sobre as células: ciclofosfamida, metot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
2
0
5
Order By: Relevance
“…Ela já foi descrita como um agente promissor em estudos in vivo e in vitro como agente antifibrótico. (11,12) Ela foi escolhida por não ser vesicante, pois acreditamos que os efeitos indesejados da MMC sobre o olho sejam principalmente devido à droga ter esse efeito. As drogas vesicantes são aquelas que provocam irritação severa com formação de vesículas e destruição tecidual quando infiltradas fora do vaso sanguíneo e podem ocasionar necrose.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ela já foi descrita como um agente promissor em estudos in vivo e in vitro como agente antifibrótico. (11,12) Ela foi escolhida por não ser vesicante, pois acreditamos que os efeitos indesejados da MMC sobre o olho sejam principalmente devido à droga ter esse efeito. As drogas vesicantes são aquelas que provocam irritação severa com formação de vesículas e destruição tecidual quando infiltradas fora do vaso sanguíneo e podem ocasionar necrose.…”
Section: Discussionunclassified
“…O protocolo para o cultivo celular foi realizado foi estabelecido anteriormente por Almodin e colaboradores (2013) (12) e baseado em Kria et al (1998). Brevemente, o tecido epitelial de pterígio foi retirado, lavado, fragmentado e dividido em três grupos: controle (sem medicação), mitomicia C e ciclofosfamida.…”
Section: Cultura De Células Epiteliais Do Pterígiounclassified
“…In a past study in 2013, Almodin et al demonstrated the effects of cyclophosphamide on fibroblasts proliferation from primary pterygium in vitro and it showed significant inhibiton of fibroblasts proliferation with no cell demage until 120 hours of drug exposition. (13) In contrast, several studies have clearly demonstrated that mitomycin C improves the surgical outcome in patients with high risk of failure; however, some postoperative complications can be linked to its use such as seidel +, ocular hypotony, maculopathy by hypotonia, shallow anterior chamber, epithelial defect, choroidal detachment, cataract and endophthalmitis. (5,(13)(14)(15)(16)(17)(18) Previous studies shows important histological changes in conjunctiva with mytomicin as inflammatory cells, myofibroblasts and goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…(13) In contrast, several studies have clearly demonstrated that mitomycin C improves the surgical outcome in patients with high risk of failure; however, some postoperative complications can be linked to its use such as seidel +, ocular hypotony, maculopathy by hypotonia, shallow anterior chamber, epithelial defect, choroidal detachment, cataract and endophthalmitis. (5,(13)(14)(15)(16)(17)(18) Previous studies shows important histological changes in conjunctiva with mytomicin as inflammatory cells, myofibroblasts and goblet cells. (19,20) Through these and other studies in the literature as Liang et al conducted a study to evaluate the histopathology of a functioning filtrating bleb of a trabeculectomy with mitomycin-c. (21) The purpose of this study was to evaluate by biomicroscopy the effect of the cyclophosphamide subconjunctival injections in rabbit as a preliminary study to verify the safety of this drug, and the possibility to be used in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo in vitro previamente publicado pelo nosso grupo, foi observada uma ação inibitória da proliferação dos fibroblastos após o tratamento com CF, sugerindo que essa droga possa ser uma alternativa à MMC. Além disso, a CF é uma droga antimitótica que não induz necrose celular, podendo ser mais segura que a MMC e com menos efeitos colaterais (20). Nosso grupo ainda demonstrou, em um trabalho publicado em 2021, os efeitos da CF subconjuntival em olhos de coelhos.…”
Section: Introductionunclassified